Effects of load mass and position on the dynamic loading of the knees, shoulders and lumbar spine during lifting: a musculoskeletal modelling approach. (October 2021) - Skals, Sebastian; Bláfoss, Rúni; de Zee, Mark; Andersen, Lars Louis; Andersen, Michael Skipper
Abstract: Musculoskeletal models may enhance our understanding of the dynamic loading of the joints during manual material handling. This study used state-of-the-art musculoskeletal models to determine the effects of load mass, asymmetry angle, horizontal location and deposit height on the dynamic loading of the knees, shoulders and lumbar spine during lifting. Recommended weight limits and lifting indices were also calculated using the NIOSH lifting equation. Based on 1832 lifts from 22 subjects, we found that load mass had the most substantial effect on L5-S1 compression. Increments in asymmetry led to large increases in mediolateral shear, while load mass and asymmetry had significant effects on anteroposterior shear. Increased deposit height led to higher shoulder forces, while the horizontal location mostly affected the forces in the knees and shoulders. These results generally support the findings of previous research, but notable differences in the trends and magnitudes of the estimated forces were observed. Highlights: Musculoskeletal model analysis of 1832 lifts performed by 22 healthy subjects. Load mass had the most substantial effect on the L5-S1 compression force. Asymmetry angle had the largest effect on the L5-S1 mediolateral shear force. Horizontal location significantly affected knee and shoulder joint reaction forces. Increments in deposit height linearly increased shoulder joint reaction forces.